'The Darker Side of Durban': South African Crime Fiction and Indian Ocean Underworlds. Issue 3 (3rd May 2016) - Lavery, Charne
Abstract : Ad hoc, illegal and invisible links between the coasts and countries of the Indian Ocean persist in the late 20th and 21st centuries. These can be discerned, from the perspective of South Africa, through a reading of their fictional traces. Rather than considering the more established canon of South African Indian writing, which elaborates familial and migratory links to south Asia, I discuss connections of illegality that appear in the resurging genre of South African crime fiction. Trevor Corbett's Allegiance (2012) and Mike Nicol and Joanne Hichens' Out to Score (2009) map Durban and Cape Town, respectively, as deeply oceanic, port-dominated cities, connected through networks of smuggling and terror to distant Indian Ocean coasts. They reveal the flip side to the Indian Ocean carceral archipelago – networks of crime implied by networks of punishment. In so doing, producing, alongside the legal Indian Ocean world of trade and travel, the figure of an Indian Ocean underworld. Indian Ocean fiction from further afield – Lindsey Collen's Boy (2005) and Abdulrazak Gurnah's The Last Gift (2012) – set up the Indian Ocean underworld as a critical lens through which the South African crime fiction can be read. Focusing on the underworld therefore provides a way not only of uncovering recent Indian Ocean history, but also of drawing together Indian Ocean with southern African studies.